Preparation method of high-strength and high-toughness shell-imitation transparent composite material
The graphene oxide-silica nanosheet structural units were prepared by liquid phase synthesis method and vacuum-assisted suction filtration method, and high-strength, high-strength, high-strength, high-strength, high-strength, and high-light translucency of the existing transparent materials were solved, and the high strength, high toughness and high light transmittance of the material were achieved.
Patent Information
- Application Number
- CN202311126698.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-09-04
AI Technical Summary
The existing transparent materials have shortcomings in mechanical properties and optical properties, and it is difficult to meet the needs of industries, construction, electronic devices and military fields.
Graphene oxide-silica nanosheet structural units were prepared by liquid phase synthesis, and composite materials with imitation shell structures were prepared by vacuum-assisted suction filtration method, and finally high-strength and high-strength imitation shell transparent composite materials were obtained through high-temperature sintering.
It achieves high strength, high toughness and high light transmission of the material, breaking through the bottleneck that it is difficult to synchronously improve the strength and toughness of traditional transparent composite materials.
Smart Images

Figure CN117164352B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials, and relates to technical fields such as nanomaterials, bionics, and optics, and specifically to a method for preparing a high-strength and high-toughness shell-like transparent composite material. Background Art
[0002] Transparent materials are widely used in industries such as industry, construction, electronic devices, and the military. These application scenarios require materials to have both excellent mechanical properties and optical properties. Currently, commonly used transparent materials are divided into two categories: inorganic glass and transparent polymers. However, inorganic glass is prone to brittle fracture, and transparent polymers have poor mechanical properties. Both are difficult to meet actual needs, thus limiting the application scope of transparent materials. The new transparent composite material combines the advantages of inorganic glass and transparent polymers. It can not only effectively overcome the brittleness of inorganic glass and the low surface hardness of transparent polymers, but also introduce new properties while obtaining excellent mechanical properties, such as thermal insulation properties, electrical properties, etc., to achieve functional applications of transparent composite materials.
[0003] Composite materials are favored by people because they can combine the multiple properties of different component materials. Shells with multi-level structures in nature are typical representatives of natural composite materials. After hundreds of millions of years of development and evolution, they embody a perfect combination of structure and performance. From a microscopic structural point of view, shells are composed of calcium carbonate and organic matter. Due to the unique "brick-mud" structure, they have high strength and good toughness, balancing the contradiction between strength and toughness. It has become a model structure for the preparation of high-strength and high-toughness layered composite materials, and also provides us with new ideas for the preparation and research of high-strength and high-toughness transparent composite materials.
[0004] In recent years, people have tried to imitate the microstructure of shells to prepare transparent composite materials with excellent performance. At present, a variety of technologies for preparing shell-like transparent composite materials have been developed, such as layer-by-layer assembly method, laser engraving method, centrifugal method, etc. The most common layer-by-layer assembly method is to form a shell-like transparent composite material by alternately assembling two or more interacting components. This assembly technology can prepare composite materials with fine and controllable size. However, this process requires continuous repetitive steps to construct a material of a certain thickness, and the process is relatively complicated. Therefore, it is urgent to develop a simple technology for preparing high-strength and high-toughness bionic transparent composite materials. Summary of the invention
[0005] The purpose of the present invention is to address the shortcomings of existing preparation methods, and to innovatively propose a method for preparing a high-strength and high-toughness shell-like transparent composite material using widely used graphene oxide and simple and stable silicon oxide as raw materials, which is simple to operate, pollution-free, mild in experimental conditions and universal. The present invention obtains graphene oxide-silicon dioxide nanosheet structural units by a simple liquid phase synthesis method, and then prepares a composite material with a shell-like structure by means of a vacuum-assisted filtration method, and finally obtains a high-strength and high-toughness shell-like transparent composite material by high-temperature sintering. It comprises the following steps:
[0006] The first step is to add 0.5-5L of anhydrous ethanol and 10-700mg of graphene oxide (GO) into a beaker and stir at room temperature to obtain a uniformly dispersed brown-yellow suspension; then add 120-150mL of ammonia water and 500-800μL of tetraethyl silicate into the beaker in sequence and stir at room temperature for 3-5h;
[0007] In the second step, the reaction solution obtained in the first step is centrifuged at 8000 r / min for 5 minutes, the obtained precipitate is washed twice with anhydrous ethanol and deionized water respectively, and then the aqueous dispersion of the substance is ultrasonicated for 10-30 minutes to obtain a uniformly dispersed graphene oxide-silicon dioxide nanosheet dispersion;
[0008] The third step is to weigh 0.6-0.8g of tetraethyl silicate, 0.1-0.3g of aluminum chloride, and 0.03-0.05g of boric acid into a beaker using an analytical balance, and then add 10mL of deionized water and stir at room temperature for 3-6h to dissolve to obtain a transparent colorless solution;
[0009] Step 4: Weigh 20-800 mg of organic matter using an analytical balance, add deionized water and stir to obtain a uniform solution;
[0010] Step 5: Use a pipette to measure 1-3 mL of the solution obtained in step 3 and 6-10 mL of the solution obtained in step 4 into a 50 mL beaker, then add 30 mg of the dispersion obtained in step 2, and then dilute to 20 mL with deionized water. Stir at room temperature for 12-36 hours, and then use vacuum assisted filtration to extract the film to finally obtain a black film sample.
[0011] In the sixth step, the film sample obtained in the fifth step is placed in a tube furnace, calcined at 600-700° C. for 1 hour, and then heated to 800-1200° C. for calcination for 1 hour, to finally obtain a transparent composite film sample.
[0012] In the present invention, unless otherwise specified, the drugs used can be used directly without further purification.
[0013] In the present invention, unless otherwise specified, the devices, instruments, equipment, materials, processes, methods, steps, preparation conditions, etc. used are those conventionally used in the art or can be easily obtained by a person of ordinary skill in the art according to the techniques conventionally used in the art.
[0014] Furthermore, in the second step, the centrifugal speed is 8000r / 5min, and the precipitate obtained by centrifugation is washed twice with anhydrous ethanol and deionized water respectively.
[0015] Furthermore, the organic matter in the fourth step can form a certain adhesion with silicon oxide, and polyvinyl alcohol, sodium carboxymethyl cellulose or chitosan can be selected.
[0016] Furthermore, the film samples prepared in the fifth step have a thickness of 2-50 μm, and the nanosheets inside the film are densely stacked to form an orderly arranged layered structure similar to the nacre of shells.
[0017] Furthermore, in the sixth step, the heating rate of the tubular furnace is 5°C / min when calcining at 600-700°C, and the heating rate of the tubular furnace is 3°C / min when calcining at 800-1200°C. The calcination temperature is preferably 950-1150°C.
[0018] Furthermore, the sample after programmed temperature-controlled sintering is a transparent film with a thickness of 1-25 μm.
[0019] Furthermore, the shell-like transparent composite material prepared by the method has a tensile strength of 1-25 MPa, a hardness of 0.1-0.35 GPa, a Young's modulus of 0.2-2 GPa, and a transmittance of more than 80% within a wavelength range of 400-800 nm.
[0020] Compared with the existing preparation strategies of high-strength and high-toughness shell-like transparent composite materials, the present invention has the following advantages:
[0021] 1. The raw materials used in the preparation process of the present invention are simple, easy to obtain, low in cost, green and environmentally friendly, and the entire preparation process is simple to operate and has universal applicability.
[0022] 2. The transparent film composite material prepared by the present invention is prepared by vacuum-assisted filtration of graphene oxide-silicon dioxide nanosheets, and its microstructure is an ordered layered structure similar to the pearl layer of shells, and the film thickness is between 1-25 μm. The material prepared by the present invention has high strength, high toughness and high light transmittance, which synergistically improves the strength and toughness of the composite material, breaking through the bottleneck that the strength and toughness of the transparent composite material are difficult to improve simultaneously.
[0023] 3. The preparation method of the present invention is simple and theoretically has the possibility of expanding production, thus ensuring its practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are optical photographs of the composite film before heat treatment obtained in Example 1 of the present invention and a scanning electron microscope photograph of its cross section.
[0025] Figure 2 These are optical photographs of the high-strength and high-toughness shell-like transparent composite material obtained in Example 1 of the present invention and scanning electron microscope photographs of its cross section.
[0026] Figure 3 This is a transmittance curve of the high-strength and high-toughness shell-like transparent composite material obtained in Example 1 of the present invention.
[0027] Figure 4 This is a stress-strain curve diagram of the high-strength and high-toughness shell-like transparent composite material obtained in Example 1 of the present invention.
[0028] Figure 5 These are optical photographs of the high-strength and high-toughness shell-like transparent composite material obtained in Example 2 of the present invention and scanning electron microscope photographs of its cross section.
[0029] Figure 6 These are optical photographs of the high-strength and high-toughness shell-imitation transparent composite material obtained in Example 3 of the present invention and scanning electron microscope photographs of its cross section. DETAILED DESCRIPTION
[0030] The preparation method of the high-strength and high-toughness shell-like transparent composite material is specifically described below in conjunction with the accompanying drawings and examples. However, it should be understood that these examples are only used to illustrate the present invention and do not limit the protection scope of the present invention in any way.
[0031] Example 1
[0032] Preparation method of 20 μm thick shell-like transparent film composite material
[0033] In the first step, 1.4 L of anhydrous ethanol and 70 mg of graphene oxide (GO) were added to a 2 L beaker and stirred at room temperature to obtain a uniformly dispersed brown-yellow suspension; 130 mL of ammonia water and 600 μL of tetraethyl silicate were added to the beaker in sequence, and the mixture was stirred at room temperature for 3.5 h.
[0034] In the second step, the reaction solution obtained in the first step is centrifuged at 8000 r / min for 5 minutes, the obtained precipitate is washed twice with anhydrous ethanol and deionized water respectively, and then the aqueous dispersion of the substance is ultrasonicated for 20 minutes to obtain a uniformly dispersed graphene oxide-silicon dioxide nanosheet dispersion;
[0035] The third step is to weigh 0.6 g of tetraethyl silicate, 0.1 g of aluminum chloride, and 0.03 g of boric acid into a beaker using an analytical balance, and then add 10 mL of deionized water and stir at room temperature for 3.5 h to dissolve to obtain a transparent colorless solution;
[0036] Step 4: Use an analytical balance to accurately weigh 200 mg of polyvinyl alcohol into a beaker, add 10 mL of deionized water, stir, and heat in a water bath to 80 °C for 2.5 h;
[0037] In the fifth step, 1.5 mL of the solution obtained in the third step and 6 mL of the solution obtained in the fourth step were measured with a pipette into a 50 mL beaker, and 30 mg of the dispersion obtained in the second step was added, followed by dilution to 20 mL with deionized water, stirring at room temperature for 16 h, and then vacuum filtration was used to extract the film, and finally a black film sample ( Figure 1 );
[0038] In the sixth step, the film sample prepared in the fifth step is placed in a tube furnace for programmed temperature sintering. The heating rate of the tube furnace is 5°C / min, and it is calcined at 700°C for 1 hour. Then the heating rate is adjusted to 3°C / min, and the temperature is raised to 1000°C and calcined for 1 hour. Finally, a transparent composite film sample with a thickness of 20 μm is obtained. The composite material has an orderly arranged layered structure similar to the nacre layer of shells ( Figure 2 ) and has a transmittance of more than 82% in the wavelength range of 400-800nm ( Figure 3 ).
[0039] In the present invention, a universal mechanical testing machine tensile test is used to test the mechanical properties of the shell-like transparent composite material of Example 1, the test gauge length is 5 mm, and the tensile displacement rate is 0.05 mm / min. The test results show that the tensile strength of the prepared silica-polyvinyl alcohol shell-like transparent composite material of Example 1 is ~15 MPa ( Figure 4 ).
[0040] Example 2
[0041] Preparation method of 18 μm thick shell-like transparent film composite material
[0042] In the first step, 1.4 L of anhydrous ethanol and 70 mg of graphene oxide (GO) were added to a 2 L beaker and stirred at room temperature to obtain a uniformly dispersed brown-yellow suspension; 130 mL of ammonia water and 600 μL of tetraethyl silicate were added to the beaker in sequence, and the mixture was stirred at room temperature for 3.5 h.
[0043] In the second step, the reaction solution obtained in the first step is centrifuged at 8000 r / min for 5 minutes, the obtained precipitate is washed twice with anhydrous ethanol and deionized water respectively, and then the aqueous dispersion of the substance is ultrasonicated for 20 minutes to obtain a uniformly dispersed graphene oxide-silicon dioxide nanosheet dispersion;
[0044] The third step is to weigh 0.6 g of tetraethyl silicate, 0.1 g of aluminum chloride, and 0.03 g of boric acid into a beaker using an analytical balance, and then add 10 mL of deionized water and stir at room temperature for 3.5 h to dissolve to obtain a transparent colorless solution;
[0045] Step 4: Use an analytical balance to accurately weigh 200 mg of polyvinyl alcohol into a beaker, add 10 mL of deionized water, stir, and heat in a water bath to 80 °C for 2.5 h;
[0046] Step 5: Use a pipette to measure 1.5 mL of the solution obtained in step 3 and 6 mL of the solution obtained in step 4 into a 50 mL beaker, then add 30 mg of the dispersion obtained in step 2, and then dilute to 20 mL with deionized water. Stir at room temperature for 16 h, and then use vacuum assisted filtration to extract the film to finally obtain a black film sample.
[0047] In the sixth step, the film sample prepared in the fifth step was placed in a tube furnace for programmed temperature sintering. The heating rate of the tube furnace was 5°C / min, and the film was calcined at 700°C for 1 hour. Then the heating rate was adjusted to 3°C / min, and the temperature was raised to 1100°C for calcination for 1 hour. Finally, a transparent composite film sample with a thickness of 18μm was obtained. After increasing the sintering temperature, the transmittance of the film sample was improved, and the microscopic layered structure of the film was more compact ( Figure 5 ).
[0048] Example 3
[0049] Preparation method of 15 μm thick shell-like transparent film composite material
[0050] In the first step, 1.4 L of anhydrous ethanol and 70 mg of graphene oxide (GO) were added to a 2 L beaker and stirred at room temperature to obtain a uniformly dispersed brown-yellow suspension; 130 mL of ammonia water and 450 μL of tetraethyl silicate were added to the beaker in sequence, and the mixture was stirred at room temperature for 3.5 h.
[0051] In the second step, the reaction solution obtained in the first step is centrifuged at 8000 r / min for 5 minutes, the obtained precipitate is washed twice with anhydrous ethanol and deionized water respectively, and then the aqueous dispersion of the substance is ultrasonicated for 20 minutes to obtain a uniformly dispersed graphene oxide-silicon dioxide nanosheet dispersion;
[0052] The third step is to weigh 0.6 g of tetraethyl silicate, 0.1 g of aluminum chloride, and 0.03 g of boric acid into a beaker using an analytical balance, and then add 10 mL of deionized water and stir at room temperature for 3.5 h to dissolve to obtain a transparent colorless solution;
[0053] Step 4: Use an analytical balance to accurately weigh 200 mg of polyvinyl alcohol into a beaker, add 10 mL of deionized water, stir, and heat in a water bath to 80 °C for 2.5 h;
[0054] Step 5: Use a pipette to measure 1.5 mL of the solution obtained in step 3 and 6 mL of the solution obtained in step 4 into a 50 mL beaker, then add 30 mg of the dispersion obtained in step 2, and then dilute to 20 mL with deionized water. Stir at room temperature for 16 h, and then use vacuum assisted filtration to extract the film to finally obtain a black film sample.
[0055] In the sixth step, the thin film sample prepared in the fifth step was placed in a tube furnace for program temperature control sintering. The heating rate of the tube furnace was 5°C / min, and it was calcined at 700°C for 1 hour. Then the heating rate was adjusted to 3°C / min, and the temperature was raised to 1000°C for calcination for 1 hour. Finally, a transparent composite film sample with a thickness of 15μm was obtained. As the amount of silicon source added decreased, the thickness of a single nanosheet became thinner, and the thickness of the composite film sample finally became thinner, and the transmittance was significantly improved ( Figure 6 ).
Claims
1. A method for preparing a high-strength and high-toughness shell-like transparent composite material, characterized in that The following steps are involved: The first step is to add 0.5-5L of anhydrous ethanol and 10-700mg of graphene oxide (GO) into a beaker and stir at room temperature to obtain a uniformly dispersed brown-yellow suspension; then add 120-150mL of ammonia water and 500-800μL of tetraethyl silicate into the beaker in sequence and stir at room temperature for 3-5h; In the second step, the reaction solution obtained in the first step is centrifuged at 8000 r / min for 5 minutes, the obtained precipitate is washed twice with anhydrous ethanol and deionized water respectively, and then the aqueous dispersion of the substance is ultrasonicated for 10-30 minutes to obtain a uniformly dispersed graphene oxide-silicon dioxide nanosheet dispersion; The third step is to weigh 0.6-0.8g of tetraethyl silicate, 0.1-0.3g of aluminum chloride, and 0.03-0.05g of boric acid into a beaker using an analytical balance, and then add 10mL of deionized water and stir at room temperature for 3-6h to dissolve to obtain a transparent colorless solution; The fourth step is to weigh 20-800 mg of an organic substance using an analytical balance, add deionized water and stir to obtain a uniform solution; the organic substance is polyvinyl alcohol, sodium carboxymethyl cellulose or chitosan; Step 5: Use a pipette to measure 1-3 mL of the solution obtained in step 3 and 6-10 mL of the solution obtained in step 4 into a 50 mL beaker, then add 30 mg of the dispersion obtained in step 2, and then dilute to 20 mL with deionized water. Stir at room temperature for 12-36 hours, and then use vacuum assisted filtration to extract the film to finally obtain a black film sample. In the sixth step, the film sample obtained in the fifth step is placed in a tube furnace, calcined at 600-700° C. for 1 hour, and then heated to 800-1200° C. for calcination for 1 hour, to finally obtain a transparent composite film sample.
2. The method for preparing a high-strength and high-toughness shell-like transparent composite material according to claim 1, characterized in that: The thickness of the thin film composite material prepared in the fifth step is 2-50 μm, and the nanosheets inside the film are densely stacked to form an ordered layered structure similar to the nacre of a shell.
3. The method for preparing a high-strength and high-toughness shell-like transparent composite material according to claim 1, characterized in that: In the sixth step, the heating rate of the tubular furnace is 5°C / min when calcining at 600-700°C, and the heating rate of the tubular furnace is 3°C / min when calcining at 800-1200°C.
4. The method for preparing a high-strength and high-toughness shell-like transparent composite material according to claim 1, characterized in that: The sample prepared in the sixth step is a transparent film composite material with a thickness of 1-25 μm. The shell-like transparent composite material prepared by this method has a tensile strength of 1-25 MPa, a hardness of 0.1-0.35 GPa, a Young's modulus of 0.2-2 GPa, and a transmittance of more than 80% in the wavelength range of 400-800 nm.